The Impact of the Bologna Reform on Student Outcomes: Evidence from Exogenous Variation in Regional Supplyof Bachelor Programs in Germany - Bernhard Enzi; Benedikt Siegler (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2016)
How did the introduction of the Bachelor-degree system affect students in Germany? Combining rich data on university students with administrative data on universities' study programs, we exploit variation in the timing of Bachelor-degree implementation across departments. To account for endogeneity in students' enrollment decisions, we apply an instrumental-variable approach based on the distance differential between an individual's nearest universities with a Bachelor's and a traditional degree program. Overall, we do not find reform effects on students' mobility, dropout, and internship participation, although there is indication that the reform reduced dropout for females and for high-achieving students and increased study satisfaction.
Keywords: I28; I21; H75; 330; Bologna Reform; Bachelor introduction; student outcomes; instrumental variables